A protocol for subsampling Late Quaternary coprolites for multi-proxy analysis. (15th April 2016) - Wood, Jamie R.; Wilmshurst, Janet M.
Abstract: The study of Late Quaternary coprolites can provide unique insights into various aspects of the biology and ecology of extinct species and prehistoric humans. Coprolite studies are becoming increasingly multi-disciplinary, allowing a greater amount of information to be obtained from individual specimens. Subsampling is a critical part of multi-proxy coprolite analysis, yet no standardised subsampling protocols exist, and details of subsampling methods have rarely been reported in published studies. Here, we outline a procedure for the subsampling of coprolites for multi-proxy analysis. The method is designed to minimise the risk of sample contamination for sensitive analyses (e.g. ancient DNA, palynology), thereby maximising the robustness of interpretations made from the results. We also stress the need for voucher samples to be retained to ensure the repeatability of results and allow for further analytical methods to be applied to specimens in the future. Graphical abstract: Highlights: Subsampling protocols are important in coprolite studies yet rarely reported. We present a protocol for subsampling coprolites for multi-proxy analysis. The protocol is designed to minimise the risk of sample contamination.